PIC16F84 based morse code reader - Abdul Aziz, Norazizul Hakimin (2002)
The principle objective of this thesis is to design Micro controller Based Morse Code Reader (MBMCR) using a Programmable Interface Controller (PIC) from Microchip. The PIC controller simplifies the overall task by providing a useful used because it is the only one supported with an EEPROM. Also, it provides the necessary functions that are associated with the system design. The system design is an integration of both hardware and a program element. The hardware portion consists of four main parts that is transistor amplifier, NE 567 Tone Detector, PIC 16F84 and LCD HD 44780. The software occupies more important part in this project which is supported by a PIC micro controller assembly language. This interfacing devices is included in the PIC micro controller that make communication possible between the PIC micro controller and the computer when programming. Though software program can be written using Basic or C- language, the assembly language supported by the PIC is chosen because It uses less program space of the already limited memory space.